The Role of the Teacher in Implementing Christian Religion Education in Growing Christian Faith for Early Age Children - Bangun Munthe; Tumpal Sirait; Bangun Bangun; Sorta Sihombing (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This study explores the role of the teacher in implementing Christian religious education for early age children and its impact on their spiritual development. A qualitative research approach was employed, and data was gathered through interviews with teachers who specialize in Christian religious education. The participants were selected from different denominations to provide a broader perspective. The findings suggest that the role of the teacher is crucial in developing a strong faith foundation for children, and that effective teaching strategies, such as storytelling, can help to make religious education engaging and relatable. The study also emphasizes the importance of working together with parents to create a supportive and nurturing environment that encourages children to develop a strong faith foundation. The results of this study provide insights into the potential lifelong impact of religious education on the spiritual development of early age children and underscore the important role that teachers play in facilitating this process